2007
DOI: 10.1158/1535-7163.mct-06-0684
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3/RhoA/ROCK signaling pathway is involved in adhesion-mediated drug resistance of multiple myeloma in an autocrine mechanism

Abstract: Adhesion of myeloma cells to bone marrow stromal cells is now considered to play a critical role in chemoresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 54 publications
3
63
1
3
Order By: Relevance
“…WNT-3, which typically activates WNT/␤-catenin signaling, was also shown to induce WNT/RHO signaling in an autocrine way in melanoma cells. In contrast to those findings on WNT/RAC signaling as a component of the WNT/␤-catenin pathway, WNT-3 was shown to activate RHO-A/ROCK signaling in an LRP5/ 6-independent manner (Kobune et al, 2007). In summary, this strongly indicates that WNTs, which generally activate WNT/␤-catenin signaling, are able to induce ␤-catenin-and LRP5/6-independent pathways in parallel.…”
Section: Wnt/rac and Wnt/rhocontrasting
confidence: 85%
See 1 more Smart Citation
“…WNT-3, which typically activates WNT/␤-catenin signaling, was also shown to induce WNT/RHO signaling in an autocrine way in melanoma cells. In contrast to those findings on WNT/RAC signaling as a component of the WNT/␤-catenin pathway, WNT-3 was shown to activate RHO-A/ROCK signaling in an LRP5/ 6-independent manner (Kobune et al, 2007). In summary, this strongly indicates that WNTs, which generally activate WNT/␤-catenin signaling, are able to induce ␤-catenin-and LRP5/6-independent pathways in parallel.…”
Section: Wnt/rac and Wnt/rhocontrasting
confidence: 85%
“…WNT-3A mediates cellular migration through DVL, RHO-A, and ROCK (Kishida et al, 2004;Endo et al, 2005;Kobune et al, 2007). Furthermore, RAC and the GEF DOCK4 are required for WNT/ ␤-catenin signaling, more precisely for the nuclear translocation of ␤-catenin (Upadhyay et al, 2008;Wu et al, 2008).…”
Section: Wnt/rac and Wnt/rhomentioning
confidence: 99%
“…20 Moreover, ZOL inhibited small G-proteins, 20 which suggests that ZOL may play an indirect role in chemoresistence. 21 Bisphosphonates also have demonstrated synergistic cytotoxic or cytostatic effects when administered in combination with chemotherapy agents. 17,[22][23][24][25][26][27][28][29][30][31][32][33] In human primary BC cells, concomitant exposure to ibandronate or ZOL plus cyclophosphamide combined with methotrexate and 5-fluorouracil or epirubicin combined with cyclophosphamide, paclitaxel, or docetaxel enhanced the cytostatic effects compared with chemotherapy alone.…”
Section: Direct Anticancer Effectsmentioning
confidence: 99%
“…Recent studies have reported that altered WNT/β-catenin signaling can change the sensitivity of tumor cells to therapeutic drugs (21)(22)(23)(24), yet potential roles for β-catenin-independent WNT signaling in drug resistance are not well understood. In the present study, we found that WNT5A protein and transcript levels were dramatically increased in BRAFi-resistant cell lines and in patient tumors.…”
Section: Introductionmentioning
confidence: 99%